Challenges to Identifying and Managing Intangible Cultural Heritage in Mauritius, Zanzibar and Seychelles (Book collections on Project MUSE., 2008)
Africa is richly blessed with cultural and natural heritage, key resources for nation building and development. Unfortunately, heritage is not being systematically researched or recognised, denying Africans the chance to learn about and benefit from heritage initiatives. This book offers a preliminary discussion of factors challenging the management of intangible cultural heritage in the African communities of Zanzibar, Mauritius and Seychelles. These islands are part of an overlapping cultural and economic zone influenced by a long history of slavery and colonial rule, a situation that has produced inequalities and underdevelopment. In all of them, heritage management is seriously underfinanced and under-resourced. African descendant heritage is given little attention and this continues to erode identity and sense of belonging to the nation. In Zanzibar tensions between majority and minority political parties affect heritage initiatives on the island. In Mauritius, the need to diversify the economy and tourism sector is encouraging the commercialisation of heritage and the homogenisation of Creole identity. In Seychelles, the legacy of socialist rule affects the conceptualisation and management of heritage, discouraging managers from exploring the island's widerange of intangible heritages. The author concludes that more funding and attention needs to be given to heritage management in Africa and its diaspora. Rosabelle Boswell is a senior lecturer in the Anthropology Department at Rhodes University, South Africa and a specialist of the southwest Indian Ocean islands. Her research interests include ethnicity, heritage, gender and development. Boswell's PhD was on poverty and identity among Creoles in Mauritius and her most recent work is onthe role of scent and fragrances in the heritage of the Swahili islands of the Indian Ocean region.